Ideal Supervisory Framework for The Disclosure of Health Information on Ready-To-Eat Processed Foods for Consumer Protection: A Comparative Legal Study of Indonesia and Chile - Daffi Allegra Asmara; Ridha Wahyuni (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The high consumption of sugar, salt, and fat (GGL) in Indonesia contributes to the increasing prevalence of non-communicable diseases or degenerative diseases, so that the fulfillment of consumers' rights to clear information as guaranteed by Article 4 letter c of Law No. 8 of 1999 concerning Consumer Protection has become an urgent issue in the context of labeling of processed ready-to-eat foods. This study examines two problems, namely the implementation of supervision of the obligation to include health risk information based on the Decree of the Minister of Health Number HK.01.07/MENKES/301/2026 and the ideal form of implementation of such supervision through a comparison with the Chilean warning label system. The method used is normative juridical with a statutory and comparative legal approach. The results of the study indicate that the implementation of supervision in Indonesia is not optimal because the KMK does not appoint a specific supervisory agency and does not contain strict sanctions for violations of the inclusion of Nutri-Level. Based on a comparison with the Chilean warning label system regulated in Ley No. 20.606, the ideal form of supervision in Indonesia includes several elements, namely clarity of supervisory institutions, specific tiered administrative sanctions, expansion of coverage to all business actors without differentiating business scale, expansion of coverage to all business actors without differentiating business scale, and protection of vulnerable groups through a ban on the sale and promotion of high GGL products in educational environments.